Angiotensin receptor blockers are not associated with reduced inflammatory markers in the general population. Issue 10 (October 2015) - Marques-Vidal, Pedro; Vollenweider, Peter; Waeber, Gérard
Abstract : Objective: Angiotensin receptor blockers (ARBs) have been suggested to reduce inflammation in randomized controlled trials. We assessed the association between ARBs and inflammatory markers in a general population setting. Methods: This is a population-based prospective study conducted in Lausanne, Switzerland. Baseline data from 933 participants on antihypertensive drugs (424 on ARBs) was collected in 2003–2006. Follow-up data from 1120 participants (572 on ARBs) was collected in 2009–2012. C-reactive protein (CRP), interleukins 1β and 6 and tumor necrosis factor alpha (TNF-α) were assessed and categorized in quartiles. Results: At baseline, no differences were found between participants taking or not taking ARBs for all inflammatory markers studied, and this association persisted after multivariate adjustment: odds ratios (ORs) and (95% confidence interval) for being in the highest quartile of interleukin-1β, interleukin-6, TNF-α and CRP for participants on ARB compared to participants not on ARB were 1.23 (0.89–1.70), 1.26 (0.93–1.70), 1.14 (0.85–1.53) and 1.27 (0.96–1.69) respectively ( P > 0.05). These findings were further replicated in the follow-up study: OR and (95% CI) of 1.10 (0.78–1.55), 0.87 (0.64–1.19), 0.83 (0.61–1.14) and 0.91 (0.68–1.22) for interleukin-1β, interleukin-6, TNF-α and CRP respectively ( P > 0.05). Finally, no effect of ARBs was found when comparing participants who received ARBs throughout the 5.4-year follow-up with participants on other antihypertensive drugs: OR and (95% CI) of 0.93 (0.61–1.42), 0.80 (0.54–1.17), 0.86 (0.59–1.25) and 0.95 (0.67–1.35) for interleukin-1β, interleukin-6, TNF-α and CRP respectively ( P > 0.05). Conclusion: ARBs are not associated with reduced levels of inflammatory markers in the general population. Abstract : Supplemental Digital Content is available in the text